Hypoxia modulates CCR7 expression in head and neck cancers. (May 2018) - Basheer, Haneen A.; Pakanavicius, Edvinas; Cooper, Patricia A.; Shnyder, Steven D.; Martin, Lisette; Hunter, Keith D.; Vinader, Victoria; Afarinkia, Kamyar
Highlights: Under hypoxia, the expression of CCR7 is elevated in both in vitro and in vivo models. There is a correlation between HIF-1α and CCR7 in all head and neck clinical stages. Hypoxia contributes to a metastatic phenotype in HNC by upregulating CCR7. Abstract: Background: The chemokine receptor CCR7 is expressed on lymphocytes and dendritic cells and is responsible for trafficking of these cells in and out of secondary lymphoid organs. It has recently been shown that CCR7 expression is elevated in a number of cancers, including head and neck cancers, and that its expression correlates to lymph node (LN) metastasis. However, little is known about the factors that can induce CCR7 expression in head and neck cancers. Method: We compared the protein expression and functional responses of CCR7 under normoxia and hypoxia in head and neck cancer cell lines OSC-19, FaDu, SCC-4, A-253 and Detroit-562 cultured as monolayers, spheroids, and grown in vivo as xenografts in balb/c mice. In addition, we analysed the correlation between hypoxia marker HIF-1α and CCR7 expression in a tissue microarray comprising 80 clinical samples with various stages and grades of malignant tumour and normal tissue. Results: Under hypoxia, the expression of CCR7 is elevated in both in vitro and in vivo models. Furthermore, in malignant tissue, a correlation is observed between hypoxia marker HIF-1α and CCR7 across all clinical stages. This correlation is also strong in early histological grade of tumours. Conclusion: Hypoxia plays a role in the regulation of the expression of CCR7 and it may contribute to the development of a metastatic phenotype in head and neck cancers through this axis.